'Drug dogs unleashed': An historical and political account of drug detection dogs for street-level policing of illicit drugs in New South Wales, Australia. Issue 3 (September 2017) - Lancaster, Kari; Hughes, Caitlin; Ritter, Alison
This article provides an historical and descriptive account of the introduction and development of the use of drug detection dogs as a tool for street-level illicit drugs policing in one Australian jurisdiction, NSW. Within this account, the legal and political context in which drug detection dogs emerged and gained prominence is described. The introduction of drug detection dogs was contingent on the political imperatives at work throughout the 1990s in NSW, and the increased salience of both policing and illicit drugs issues at this time. In documenting the emergence of the use of drug detection dogs from the early 2000s, and the associated legal challenges and rapid legislative responses, the role of third sector organisations and the media in generating debate is notable. Debates concerning the dogs' effectiveness emerged in the mid- to late-2000s, giving rise to anomalies between policy and evidence. The more recent legislative developments and public and political debate about drug detection dogs from 2012 to 2014 can be seen in light of this history. By taking a different view which situates decisions and events in their historical and political context, we begin to see the dynamic processes and contingency involved in the development and implementation of particular illicit drugs policing policies over time. As debate about drug detection dogs continues to play out, generating new insights into drugs policing policy processes is imperative.